Numerical simulation of particle motion at cucumber straw grinding process based on EDEM - Xu, Yunfeng; Zhang, Xiliang; Wu, Shuo; Chen, Cheng; Wang, Jizhang; Yuan, Shouqi; Chen, Bin; Li, Pingping; Xu, Rongjun (International Journal of Agricultural and Biological Engineering, 2020)
Simulation of straw grinding process based on discrete element method (DEM) was proposed. According to the force analysis and kinematics analysis, the differential equation of straw particle motion on hammers was deduced, and the formation mechanism of the material circulation layer was obtained. Geometric model of grinder, particle model and contact model were established by EDEM software. The influence of hammer number, hammer thickness and gap of the hammer-sieve on particle grinding number and power consumption were obtained by single factor simulation test. The grinding process is divided into three stages. The hammer smashing plays a dominant role in 0-0.25 s. While the hammer smashing particle number increases slowly and then decreases to the lowest level in 0.25-0.60 s, the tooth plate smashing particle number increases rapidly and dominates, and then forming a material circulation layer. The hammer and tooth plate smashing particle number is basically stable in 0.60-2.00 s, and the tooth plate smashing occupies the dominant position. With the increase of the number and thickness of hammers, the power consumption of crusher tends to increase, and with the increase of the gap between hammers and sieves, the power consumption of crusher decreases first and then increases. The results can provide guidance for the development of high-efficiency and energy-saving grinding equipment for cucumber straw. Keywords: cucumber straw, grinding process, particle motion, numerical simulation, EDEM DOI: 10.25165/j.ijabe.20201306.5452 Citation: Xu Y F, Zhang X L, Wu S, Chen C, Wang J Z, Yuan S Q, et al. Numerical simulation of particle motion at cucumber straw grinding process based on EDEM. Int J Agric & Biol Eng, 2020; 13(6): 227–235.